STRATEGI PENGELOLAAN OBYEK DAN DAYA TARIK WISATA DI KABUPATEN KOTABARU - Ibnu Faozi; Muhammad Rezki Oktaviannoor (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2019)
The aims of this study were 1) to find out how the bargaining value of the Tourism Objects and Attractions that already exist to tourists, 2) to find out what strategies can be done to the existing Tourism Objects and Attractions to attract tourists to Kotabaru Regency. This study used descriptive qualitative method. Data collection were carried out in four ways, namely observation, FGD (Focus Group Discussion) interviews and documentation. The results of this study were 1) Tourism Object of Teluk Tamiang Village, the current bargaining value is still low, the strategies used are not coherent, and there are still strategic contradictions, 2) Five technical strategies need to be done, namely increasing road access to the summit of Mount Lekke Tedong, providing sleep equipment, ensuring adequate sanitation facilities and clean conditions, selling Bay Tamiang Village tour packages with an all-in-one payment system, making a place to eat out door, 3) The Government of Teluk Tamiang Village needs to allocate Village Funds to improve tourism support facilities, 4) Encourage community to form a Tourism Awareness Group (Pokdarwis) in Teluk Tamiang Village in order to be able to foster residents whose homes are used as tourist accommodation to provide services and provide comfortable facilities.